Women's perceptions of women's roles: A study of female welfare clients - Waxler, Ilene; Columbia University (1980)
This study was undertaken to explore the perceptions of women's roles of a group of unattached, employable female welfare recipients and the relationship of these perceptions to self-image and employment. The intractable unemployment rate among these welfare women which gave rise to this study may in part be a function of the findings that they feel they are being forced into a position which is less socially acceptable. The major questions in the study involved the connections between various demographic variables within this group and their possible effects on perception, self-image and view of employment. The sample consisted of 172 female welfare clients, chosen so that the major ethnic groups would be represented, out of a population of 2,000 such single welfare women who had active cases at an Employment Eligibility Center in New York City. The instrument consisted mainly of a questionnaire that had been used previously with middle-class and professional women.
The sections were to be responded to first, the way one feels; second, the way an ideal women would feel; and third, the way a man's ideal women would feel. To these sections were added questions having to do with job seeking and attitudes toward work. From the first three sections an index of intra-familial or extra-familial satisfaction was established for each respondent. The findings indicate that, overall, this group of clients took a much more extra-familial position than the prior groups of respondents. When tests were made by mean scores and ethnic group it was found that there were significant differences, with Black women scoring more extra-familial (positive score) on "own self" and "ideal woman" than either white or Hispanic women while Hispanic women scored least positive (more intra-familial). In general the younger and more educated the woman, the more likely she was to find satisfaction from endeavors outside of the family.
After the findings were established on the first three sections of the instrument, they were compared and coordinated with a review of work histories and a survey of certain beliefs the sample held about employment. Strong conflict was suggested in relation to employment and receipt of Public Assistance bespeaks ongoing difficulty in the world of work. The problem of generational dependency means that there can be no simple answer as to how social services can help them to break the familiar pattern and go forward. Since the barriers to employment are very complex, use might be made of the recognized socially acceptable female role and the socialization that most women have had. A work/training program that was imitative of their school experience might provide them with the security needed to reduce anxiety levels. In selecting appropriate training opportunities and seeking job placement, the attitude of the women to extra- and intra-familial roles can be relevant.
(UnM)AAI8028814
Source: Dissertation Abstracts International, Volume: 41-07, Section: A, page: 3298.
Thesis (D.S.W.)--Columbia University, 1980.
Microfiche.
Keywords: Women's Studies